1992
DOI: 10.1111/j.1464-5491.1992.tb01880.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weight‐bearing Pressure on the Plantar Circulation in Diabetes Mellitus

Abstract: Patients with diabetic neuropathy are prone to ulceration on the sole of the foot, especially in areas with high weight-bearing pressure. The relationship between weight-bearing pressure and nutritive skin circulation in the plantar region was studied. Gait analysis was performed with the EMED Gait Analysis System and the skin circulation was measured by fluorescein flowmetry in ten neuropathic diabetic patients and in eight healthy controls. The critical plantar foot pressure above which nutritional blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This is in line with previous suggestions by Smith et al [20]. Decreased shock absorption capacity may be crucial to the development of neuropathic foot ulcers, since neither impaired circulation [17] during plantar pressure application, nor abnormally high plantar pressure alone [15,20] was found to be associated to foot ulceration. Insiduous plantar induration in a subgroup of patients would also explain the observation that not every diabetic with early polyneuropathy may develop increased plantar pressures over the metatarsal heads.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous suggestions by Smith et al [20]. Decreased shock absorption capacity may be crucial to the development of neuropathic foot ulcers, since neither impaired circulation [17] during plantar pressure application, nor abnormally high plantar pressure alone [15,20] was found to be associated to foot ulceration. Insiduous plantar induration in a subgroup of patients would also explain the observation that not every diabetic with early polyneuropathy may develop increased plantar pressures over the metatarsal heads.…”
Section: Discussionsupporting
confidence: 90%
“…The focal nature of the lesion beneath the first metatarsal head would certainly be consistent with increased plantar pressures seen in this region in the presence of diabetic neuropathy[2]. However, it has been demonstrated that increased vertical plantar pressures are insufficiently raised to impair nutritional blood flow in patients with diabetic neuropathy[13]. It has been suggested that shear forces are increased in the neuropathic foot[14], although definitive studies of their relative contribution await the development of sufficiently accurate shear force transducers.…”
Section: Discussionmentioning
confidence: 89%
“… 49 However, the clinical significance of standing for ulcer prevention and healing is not yet established. On the one hand, plantar pressure when standing often exceeds 3 N/cm 2 (30 kPa), needed to arrest nutritional blood flow in the skin, 50 especially when barefooted. 51 53 It may be speculated that because people with sensory neuropathy do not feel discomfort if blood flow is arrested, they would not shift their weight when standing to improve circulation.…”
Section: Methods To Measure Adherencementioning
confidence: 99%